Care in Crisis: Entomology and the Industrial Honey Bee - van Deelen, Grace C. (Tufts Archival Research Center, 2021)
This thesis, for the Department of Anthropology, explores how care for and about honey bees is both practiced and transformed through the structure of entomological sciences.; Advisor: Professor Alex Blanchette